g+4g-3=12

Simple and best practice solution for g+4g-3=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for g+4g-3=12 equation:


Simplifying
g + 4g + -3 = 12

Reorder the terms:
-3 + g + 4g = 12

Combine like terms: g + 4g = 5g
-3 + 5g = 12

Solving
-3 + 5g = 12

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 5g = 12 + 3

Combine like terms: -3 + 3 = 0
0 + 5g = 12 + 3
5g = 12 + 3

Combine like terms: 12 + 3 = 15
5g = 15

Divide each side by '5'.
g = 3

Simplifying
g = 3

See similar equations:

| -2v+1+2v=-7+v | | -26=x/4 | | -(x-4)=2x-7 | | -16+19q=20q | | (-2/3)x=-4/3 | | 2c+-3c=2 | | -(x+3)=9 | | 2x=19/5=3 | | 4m-3-4n=11 | | -15c+-10c+-10=-10 | | 8+6p=8+6p | | y-10=29 | | 8x-5x=30 | | 8/24=2/n | | 3(k+13)-17=-2 | | n=5p+28+4 | | 3(z+3)=7+3z-6z | | -2(2k-5)=10 | | -19=13-8y | | 3f-8=10f+9-8f | | y^4-3y^2-2y=0 | | n^2-34n+64=0 | | 2x^5+6x^4-4x^2=0 | | 1/4x-3/5=1 | | 8.1=5n-6.4 | | 6py/-5y | | -11w+w=-10 | | -2(p-10)+11=5 | | (x^2+8x)+16=25 | | 2(3x+4)=-16 | | -3d+-d=-20 | | 21k^3-18k^2+7k-6=0 |

Equations solver categories